Growth and characterization of BaBi2Nb2O9 thin films made by RF-magnetron sputtering - Mazon, T.; Joanni, E.; Fernandes, JRA; Zaghete, M. A.; Cilense, M.; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2003)
The RF-magnetron sputtering technique has been used to deposit polycrystalline thin films of layered-structured ferroelectric BaBi2Nb2O9 (BBN). The XRD patterns for the films annealed at 700degreesC for 1 hour show the presence of the BBN phase as well as the BaNb2O6 secondary phase. A better crystallization of the BBN phase and an inhibition of the secondary phase is obtained with the increase of temperature. The surface of the prepared films was rather dense and smooth with no cracks. The 300 nm thick BBN thin films exhibited a room-temperature dielectric constant of about 779 with a dissipation factor of 0.09 at a frequency of 100 kHz.
Keywords: BaBi2Nb2O9; thin films; dielectric properties; RF-magnetron sputtering